Eksistensi Pendidikan Islam di Indonesia: Analisis Terhadap Kurikulum dan Implementasinya - Murwanti; Taufik (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
In essence, Islamic education in Indonesia has been going on since the entry and development of Islam in this country. The large number of people's acceptance of Islam makes religion a pillar of life for the wider community, of course, balanced with the learning process to know and understand Islamic teachings so that it becomes evidence that Islamic education as a sub-system of national education has historical importance in the development of Indonesian education. It can be studied that Islamic education during colonialism, the independence period until the process of integrating Islamic education into the national education system is thus real, as well as being evidence of the birth of Islamic education. In fact, development is inseparable from the existence of Islamic education.